The line x - y = 4 is tangential to the circle `(x - a)^2 + y^2 = 36` if the line and the circle have only one point of contact.

x - y = 4 => y = x - 4

Substitute this in `(x - a)^2 + y^2 = 36`

=> `(x - a)^2 + (x - 4)^2 = 36`

=> `x^2 + a^2 - 2ax + x^2 + 16 - 8x = 36`

=> `2x^2 - 2ax - 8x + a^2 - 20 = 0`

This quadratic equation should have a common root. This is the case when `(-2a - 8)^2 - 4*2*(a^2 - 20) = 0`

=> `(-a - 4)^2 - 2*(a^2 - 20) = 0`

=> `a^2 + 16 + 8a - 2a^2 + 40 = 0`

=> `-a^2 + 8a + 56 = 0`

=> `a^2 - 8a - 56 = 0`

a = `(8 +- sqrt(64 + 224))/2`

= `4 +- 6*sqrt 2`

**The values of a for which the line x - y = 4 is a tangent of the circle `(x - a)^2 + y^2 = 36` are **`4 +- 6*sqrt 2`

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now